Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON) 2012
DOI: 10.1109/educon.2012.6201129
|View full text |Cite
|
Sign up to set email alerts
|

Social networks, microblogging, virtual worlds, and Web 2.0 in the teaching of programming techniques for software engineering: A trial combining collaboration and social interaction beyond college

Abstract: With the goal of lessening barriers to the learning of advanced programming techniques, we put into place a trial which required students to get involved with online communities of programmers. Using a course assignment on software architecture styles, students had study a problem, find basis for a tentative approach, and discuss it online with programmers. The expectation was that students would find motivation for their studies from both the contact with communities of programmers, and from having to study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…Compared with the previous action research cycle [29], we found that more groups actively participated in the tasks throughout the semester. In fact, 9 of the 21 groups that started the project participated regularly and obtained feedback in communities of practice online (Table 3).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Compared with the previous action research cycle [29], we found that more groups actively participated in the tasks throughout the semester. In fact, 9 of the 21 groups that started the project participated regularly and obtained feedback in communities of practice online (Table 3).…”
Section: Resultsmentioning
confidence: 67%
“…The first approach has been described in detail in an earlier paper [29]. In the first action research cycle, a course assignment on software architecture styles was used.…”
Section: Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Design Science research [15], we developed a learning approach based on problem-based learning -(PBL) [16], which was reshaped and improved throughout three iterations [5] [6]. In each iteration, new activity plans were designed, alongside with resources and tools.…”
Section: Introductionmentioning
confidence: 99%